SPECT Imaging of Acute Disc Herniation by Targeting Integrin α5β1 in Rat Models - Guan, Jian; Yuan, Chenghua; Tian, Xin; Cheng, Lei; Gao, Hannan; Yao, Qingyu; Wang, Xinyu; Wu, Hao; Chen, Zan; Jian, Fengzeng (Frontiers in Neurology, 2022)
Objective Traditional morphological imaging of intervertebral disc herniation (IVDH) is challenging in early disease diagnosis. Aiming at the early diagnosis of IVD by non-invasive molecular imaging targeting of integrin α5β1, we performed novel imaging in rats with acute IVDH for the first time. Methods Animal models were prepared by conducting an established needle puncture procedure through the normal intervertebral disc (IVD). The disc-injured rats underwent SPECT/CT imaging of the 99mTc-3PisoDGR2 peptide at 1 day to 2 months postinjury. The expression change of integrin α5β1 was determined by anti-integrin α5 and anti-integrin α5β1 immunohistochemistry (IHC). Magnetic resonance imaging (MRI) was performed for comparison during disease progression. The morphological changes of the disc were determined by safranin-O staining. Results Rats with acute IVDH showed gradually increased disc uptake of 99mTc-3PisoDGR2 from 1 to 7 days posttreatment, which was a significantly higher level than that of the normal disks in degenerative diseases. IHC results showed the expression of integrin α5β1 on the surface of annulus fibrosus (AF) cells and nucleus pulposus (NP) cells, which agreed with the uptake data. MRI showed a progressively decreased T2 density and MRI index throughout the investigation. Hematoxylin and eosin (HE) staining and safranin-O staining revealed a disorganized structure of the IVD as well as loss of proteoglycans after puncture. Conclusions The present study demonstrated a good correlation between integrin α5β1 expression and acute disc herniation. The SPECT/CT imaging of 99mTc-3PisoDGR2 targeting integrin α5β1 may diagnose IVDH in an acute phase for early disease management.